2009
DOI: 10.1051/mmnp/20094302
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Physiological and Pharmacological Control on Cell Proliferation to Optimise Cancer Treatments

Abstract: Abstract. This review aims at presenting a synoptic, if not exhaustive, point of view on some of the problems encountered by biologists and physicians who deal with natural cell proliferation and disruptions of its physiological control in cancer disease. It also aims at suggesting how mathematicians are naturally challenged by these questions and how they might help, not only biologists to deal theoretically with biological complexity, but also physicians to optimise therapeutics, on which last point the focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 257 publications
0
34
0
Order By: Relevance
“…becomes a problem with two populations, healthy and cancer, that are partly proliferating, partly dying, both evolving under the same drug insult, however with structural dynamic differences between them. This question has been the object of several studies [17,27,30,50,51,52], taking into account for some of them heterogeneity with respect to age phases in the cell division cycle [27,28,29,30], but so far heterogeneity with respect to phenotypes determining drug resistance had only been sketched as prospective work [27,51].…”
Section: Exploiting Structural Differences Between Healthy and Cancermentioning
confidence: 99%
“…becomes a problem with two populations, healthy and cancer, that are partly proliferating, partly dying, both evolving under the same drug insult, however with structural dynamic differences between them. This question has been the object of several studies [17,27,30,50,51,52], taking into account for some of them heterogeneity with respect to age phases in the cell division cycle [27,28,29,30], but so far heterogeneity with respect to phenotypes determining drug resistance had only been sketched as prospective work [27,51].…”
Section: Exploiting Structural Differences Between Healthy and Cancermentioning
confidence: 99%
“…However, this approach, obviously valuable to provide new weapons in the war against cancer, by its nature cannot take into account the constraints linked to toxicity or drug resistance issues, which must be considered at the cell population level in a whole-body drug delivery optimisation perspective. This molecular biology approach should also be completed by whole-body pharmacokineticpharmacodynamic molecular modelling to represent the fate of drugs in the organism, as sketched above and in [37,38]. In other words, these approaches may be thought of as understanding the target and the weapon, whereas, to stay in this metaphor, optimisation of drug control is training to shoot in all conditions to safely reach the target.…”
Section: Discussionmentioning
confidence: 99%
“…As sketched elsewhere [37,38], theoretic drug delivery optimisation is the last step of therapeutic optimisation, which must rely firstly on an accurate representation of the behaviour of targets (wanted and unwanted) without treatment and on the changes the means of action of the physician -drugs -exert on them.…”
Section: Discussionmentioning
confidence: 99%
“…In some structured population models of cancer, which is the main topic of this issue, the evolution along the cell cycle is related to the activation of specific signalling pathways, or to the internal molecular content, e.g., DNA (see also, in this issue, the paper by Friedman [32] and the review by Clarimbault [25], where more references can be found). In particular, in [27] the transitions through the restriction point is related to the presence of specific control proteins, e.g., cyclin/CDK complexes.…”
Section: Nested Modelsmentioning
confidence: 99%